2016
DOI: 10.1016/j.earlhumdev.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Safety of histamine-2 receptor blockers in hospitalized VLBW infants

Abstract: Background Histamine-2 receptor (H2) blockers are often used in very low birth weight infants despite lack of population specific efficacy and safety data. Aims We sought to describe safety and temporal trends in histamine-2 receptor (H2) blocker use in hospitalized very low birth weight (VLBW) infants. Study Design We conducted a retrospective cohort study using a clinical database populated by an electronic health record shared by 348 neonatal intensive care units in the United States. Subjects We incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 20 publications
(18 reference statements)
0
20
0
Order By: Relevance
“… 2 , 28 Intestinal bacteria are linked to the development of NEC because NEC occurs after colonization of the intestine has occurred, although NEC is treated with broad-spectrum antibiotics that target enteric microbes, 29 , 30 , 31 suggesting that bacterial–host signaling plays a role in NEC development. Specific clinical risk factors for NEC include the administration of acid-suppressive H2 blockers, 32 , 33 , 34 excessive antibiotic use, 35 brief episodes of hypoxia, 36 the presence of chorio-amnionitis (an infection of the lining of the uterine cavity during gestation), 37 and the administration of formula feeds. 38 , 39 The administration of breast milk is highly protective against NEC, 40 , 41 a finding that has provided the rationale for the use of donor breast milk as a specific preventive strategy, 42 , 43 and that suggests that it may be the absence of breast milk rather than the presence of formula that is most important in NEC pathogenesis.…”
Section: Clinical Risk Factors For Necmentioning
confidence: 99%
“… 2 , 28 Intestinal bacteria are linked to the development of NEC because NEC occurs after colonization of the intestine has occurred, although NEC is treated with broad-spectrum antibiotics that target enteric microbes, 29 , 30 , 31 suggesting that bacterial–host signaling plays a role in NEC development. Specific clinical risk factors for NEC include the administration of acid-suppressive H2 blockers, 32 , 33 , 34 excessive antibiotic use, 35 brief episodes of hypoxia, 36 the presence of chorio-amnionitis (an infection of the lining of the uterine cavity during gestation), 37 and the administration of formula feeds. 38 , 39 The administration of breast milk is highly protective against NEC, 40 , 41 a finding that has provided the rationale for the use of donor breast milk as a specific preventive strategy, 42 , 43 and that suggests that it may be the absence of breast milk rather than the presence of formula that is most important in NEC pathogenesis.…”
Section: Clinical Risk Factors For Necmentioning
confidence: 99%
“…Table 1 summarizes the main characteristics of the 10 studies. Five studies used a case-control design [13,2326] and five were cohorts [14,16,2729]. No clinical trials were found.…”
Section: Resultsmentioning
confidence: 99%
“…A 2014 systematic review of clinical trials conducted in 1 to 15 years old children reported that H 2 RA were effective in reducing GERD signs and symptoms, but did not report adverse effects in a measurable manner, precluding a quantitative analysis on drug safety [11]. Other studies in neonates however have shown that H 2 RA may predispose to infections [3,1214], necrotising enterocolitis (NEC) [14,15] and death [14,16], but there are no systematic analyses of this evidence.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective cohort study conducted by Romaine et al 16 in the USA concluded that H2 blocker use was associated with increased risk of the combined outcome of death, NEC or sepsis in hospitalised very low birthweight infants (VLBW). Another recent retrospective cohort study showed that ranitidine use was associated with an increased risk of infections and mortality in preterm infants, but not with NEC.…”
Section: Discussionmentioning
confidence: 99%